Behavioral Factors And Infrastructure Moderation In Household Waste Sorting: Urban-Rural Comparison In Sleman Regency - Pramudita, Alifia Farah; Herwangi, Yori (Program Studi Perencanaan Wilayah dan Kota, Fakultas Teknik, Universitas Semarang, 2025)
Waste management remains a critical environmental challenge, particularly in regions with significant urban-rural disparities. This study investigates household waste sorting behavior in Sleman Regency, Indonesia, by applying the Theory of Planned Behavior (TPB). The objectives are to examine the influence of attitude, subjective norms, and perceived behavioral control on the intention to sort waste, as well as to analyze the moderating effect of infrastructure on these relationships in urban and rural areas. A quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed, with data collected from 796 households (399 urban, 397 rural). The findings reveal that attitude, subjective norms, and perceived behavioral control significantly influence sorting intentions, with subjective norms being more impactful in urban areas, while perceived behavioral control is more influential in rural areas. Infrastructure significantly moderates the relationship between perceived behavioral control and intention in rural areas but shows no significant moderating effect in urban areas. These results highlight the necessity of context-specific strategies in waste management. The study contributes to the TPB literature by incorporating the moderating role of infrastructure and offers practical insights for policymakers to design sustainable waste management interventions tailored to urban and rural contexts.